Study on Biosorption of Divalent ion onto Treated Prosopis Juliflora Bark from Aqueous Solutions: An Approach towards Isothermal and Statistical Analysis - N. Muthulakshmi Andal; S. Charulatha; N.S. Gayathri (Challenges and Advances in Chemical Science Vol. 3, 2021)
The present work emphasizes the utilization of Prosopis juliflora bark for adsorption of Cu(II). Raw Prosopis juliflora bark is treated using 0.1N hydrochloric acid to enhance its sorption efficiency. Characterization of TPJB was carried out using Scanning Electron Microscopy, Energy Dispersive X-ray Analysis, Bruner-Emmet-Teller and Barrett-Joyner-Halenda analyses. Experimental verification for Cu(II)- TPJB through Batch mode under operating factors viz., particle sizes/ doses of the material upon a range of initial Cu(II) concentrations at different temperatures, agitation time and pH values system was conducted, where maximum amount adsorbed is found to be 43.11 mg/g (97.4%) ,under optimized conditions, its efficiency being 3 fold times more than Ce values reported by other researchers. Quantification of Treated Prosopis juliflora bark is done through column studies, wherein 98% Cu(II) removal is observed. Langmuir, Freundlich and Tempkin isothermal curves at various initial concentrations are plotted for Cu(II)-TPJB system, the straight line fit is best suited for Freundlich model. The response of Treated Prosopis juliflora bark in trapping Cu(II) ions influenced by various parameters is statistically verified using SPSS software, indicative of good correlation.